Tourism and environment case study of Fort James - Dickenson Bay, Antigua - Jackson, Ivor L (ECLAC Port-of-SpainTT, 1985)
Describes area under study highlighting its present and potential tourist use. Discusses the adverse environmental impacts of tourism and shows the extent to which the resources can sustain development. Makes recommendations on suitable ways of exploiting tourism resources with minimal harmful effects on the environment.